MODEL INTEGRATIF PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PEDULI SOSIAL SISWA MADRASAH TSANAWIYAH (Studi Multisitus Wilayah Pesawaran) - Chairul Anwar; Puji Amelia Sari; Syaiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the integrative model of Islamic religious education in shaping the socially aware character of Madrasah Tsanawiyah students in a multi-site study in the Pesawaran – Lampung region, specifically at MTS Unwanul Falah Punduh Pedada. The background of this study is the concerning phenomenon of declining empathy and social awareness among students, which is characterized by neglectful attitudes, lack of respect for teachers, and minimal participation in social activities. The purpose of this study is to analyze how the integration of Islamic values ​​in religious education can shape students’ social sensitivity, including the stages of transformation, transaction, and trans-internalization of values. The research method used is a descriptive qualitative approach, with data collection through observation, interviews, and documentation. Key informants in this study include the Principal of Madrasah, Deputy Head of Curriculum, PAI teachers (Akidah, Fiqh, Al-Qur'an Hadith, SKI), Administrative staff, and eighth grade students at MTs Unwanul Falah Punduh Pedada. This research will also be expanded with a multi-site study in the Pesawaran region to obtain a more comprehensive picture. Initial research results indicate that the internalization of Islamic values ​​at MTs Unwanul Falah has progressed through three important stages: value transformation, where teachers instill Islamic teachings through role models and inspirational stories; value transactions, which create two-way interactions to foster empathy and social responsibility; and value transinternalization, where Islamic values ​​have become an integral part of students' personalities, encouraging independence and a sense of doing good without coercion. This confirms that Islamic religious education has great potential in shaping students' socially conscious character.